2007
DOI: 10.1002/aqc.917
|View full text |Cite
|
Sign up to set email alerts
|

A conceptual model of the variation in parental attendance in response to environmental fluctuation: foraging energetics of lactating sea lions and fur seals

Abstract: ABSTRACT1. A conceptual model is described and tested using empirical data that predicts how air-breathing marine vertebrates that are tied to shore for reproduction, but feed at sea, should respond to changes in prey availability.2. The model examines the trade-off between changes in trip duration and foraging intensity as measured by field metabolic rate. It predicts that parents should increase the intensity of effort, and hence metabolic rate, prior to increasing the duration of foraging trips to maintain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
94
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 85 publications
(107 citation statements)
references
References 44 publications
12
94
1
Order By: Relevance
“…In capital breeders, size and condition are strongly correlated to reproductive effort and success (Festa-Bianchet et al 1998;Côte and Festa-Bianchet 2001;Crocker et al 2001); however, most mammals are income breeders, animals that provision offspring from current food intake. Although size and condition have been shown to be weakly correlated with reproductive effort in income breeders (Andersen et al 2000;Boyd 2000), maternal traits, provisioning strategy, and offspring traits may have a different influence on energy allocation to offspring in income breeders (Costa 1993). For example, a study of European roe deer, an income breeder, found that maternal body weight did not have a pervasive effect on maternal care, contrary to authors' predictions (Andersen et al 2000).…”
Section: Dynamic Influence Of Maternal and Pup Traits On Maternal Carmentioning
confidence: 86%
See 3 more Smart Citations
“…In capital breeders, size and condition are strongly correlated to reproductive effort and success (Festa-Bianchet et al 1998;Côte and Festa-Bianchet 2001;Crocker et al 2001); however, most mammals are income breeders, animals that provision offspring from current food intake. Although size and condition have been shown to be weakly correlated with reproductive effort in income breeders (Andersen et al 2000;Boyd 2000), maternal traits, provisioning strategy, and offspring traits may have a different influence on energy allocation to offspring in income breeders (Costa 1993). For example, a study of European roe deer, an income breeder, found that maternal body weight did not have a pervasive effect on maternal care, contrary to authors' predictions (Andersen et al 2000).…”
Section: Dynamic Influence Of Maternal and Pup Traits On Maternal Carmentioning
confidence: 86%
“…Additionally, some of the females were recaptured to collect milk samples approximately 5 d ( ), 1 mo ( ), or 2 mo postpartum ( ). n p 11 n p 10 n p 21 Milk-consumption measurements were collected from the pups of captured females at three developmental stages-perinatal (newborn, ), premolt (1 mo, ), and molt n p 48 n p 45 (2 mo, )-using the doubly labeled water (DLW) techn p 31 nique (Costa 1987b;Donohue et al 2002). Sample size decreased with pup age because some pups were lost to predation (17 pups died because of suspected leopard seal predation; one pup died of starvation).…”
Section: Field Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For mammal predators, lactation is the most energydemanding period for a female. Therefore, during this time, they must optimize their foraging behaviour to maximize energy intake to rear their offspring successfully (Gittleman and Thompson 1988;Arnould 1997;Trillmich and Weissing 2006;Costa 2007). Pinnipeds (seals and sea lions) are marine mammal predators who are often central place foraging colonial breeders which restrict their foraging range during breeding and can heighten impacts with fisheries activities as they have no alternative foraging locations.…”
Section: Introductionmentioning
confidence: 99%